The Verbless Clause in Biblical Hebrew: Linguistic Approaches - Watson, Wilfred G. E. 20./21. Jh. (Journal of Semitic studies, 2002)
The Verbless Clause in Biblical Hebrew: Linguistic Approaches Cynthia L.Miller (Linguistic Studies in Ancient West Semitic 1). EisenbraunsWinona Lake 1999iv + 368Hardback$39.50 1‐57506‐036‐1 , 1University of Newcastle